1988
DOI: 10.17763/haer.58.1.h571521105l7nm65
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Considerations: The Deep Meaning of Native American Schooling, 1880-1900

Abstract: In the mid-nineteenth century, U.S. policymakers held two conflicting visions of the Indian's future: one, that Indians as a race were doomed to extinction, and two, that Indians were capable of being "civilized" and assimilated into White society. By the end of the century,in light of the Indians' loss of land and traditional ways of life, policymakers under-took an intense campaign to assimilate Indians through schooling. David Adams argues that to see this process of schooling simply as a means of assimilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(30 citation statements)
references
References 0 publications
0
27
0
3
Order By: Relevance
“…Where African American history is tied to slavery (Banks, 2009), Native American history is tied to near genocide and attempts at assimilation. These tactics were utilized by the federal government through the residential school era (Adams, 1988;Carney, 1999) and resulted in significant mistrust (LaCounte, 1987). Both Native Americans and African Americans share a history of oppression at the hands of Whites, and both were subject to deficit ideologies in schools (Deyhle & Swisher, 1997).…”
Section: Resisting Assimilation In This Sense Means Maintaining An mentioning
confidence: 99%
“…Where African American history is tied to slavery (Banks, 2009), Native American history is tied to near genocide and attempts at assimilation. These tactics were utilized by the federal government through the residential school era (Adams, 1988;Carney, 1999) and resulted in significant mistrust (LaCounte, 1987). Both Native Americans and African Americans share a history of oppression at the hands of Whites, and both were subject to deficit ideologies in schools (Deyhle & Swisher, 1997).…”
Section: Resisting Assimilation In This Sense Means Maintaining An mentioning
confidence: 99%
“…By the second half of the sixteenth century, the notion of civility acquired new meanings in addition to manners (Huppert, 1971). Resembling the core meanings of the eighteenth-century concept of civilization, civility came to be associated with a general theory of historical evolution (from the original state of nature) within a civilized/savagism paradigm (Huppert, 1971;Adams, 1988).…”
Section: Modernity and Colonialitymentioning
confidence: 99%
“…This was seen by U. S. policy makers as an ethical alternative to the extermination or extinction of Native American peoples after the achievement of "manifest destiny"-the 19 th century view that the United States was destined to conquer and absorb North American territory from the east coast to the west coast, dominating the continent economically and politically. In exchange for the loss of their home lands and through the agency of Western-centric education, the American Indians were to be stripped of their cultures and their languages and transformed into farmers, trades people, or crafts people, so that they could take their place in the society of White Americans (Adams, 1988;Adams, 1995;DeJong, 1993;Lomawaima, 1995;Noriega, 1992;Reyhner, 1992). This educational task was to be accomplished by a system of boarding schools deliberately designed to keep Native children away from the recidivist influences of their homes and tribes for long periods of time, so that the effects of Western-centric education and indoctrination might have maximum effect.…”
Section: Native American Concerns For Educationmentioning
confidence: 99%
“…Some Native Americans accommodated to White man's education in order to gain the ability to survive in a world dominated by European Americans, while others actively resisted all attempts at forced assimilation. Many Native Americans who succumbed to the assimilationist agenda found that they were accepted by neither European American nor Native American society (Adams, 1988;Adams, 1995;DeJong, 1993;Reyhner, 1992).…”
Section: Native American Concerns For Educationmentioning
confidence: 99%